Decolourisation Capabilities of Ligninolytic Enzymes Produced by Marasmius cladophyllus UMAS MS8 on Remazol Brilliant Blue R and Other Azo Dyes - Ngieng, Ngui Sing; Ahmad, Husaini; Azham, Zulkharnain; Hairul Azman, Roslan (Hindawi Publishing Corporation, 2017)
Marasmius cladophyllus was examined for its ability to degradatively decolourise the recalcitrant dye Remazol Brilliant Blue R (RBBR) and screened for the production of ligninolytic enzymes using specific substrates. Monitoring dye decolourisation by the decrease in absorbance ratio of A 592/A 500 shows that the decolourisation of RBBR dye was associated with the dye degradation. Marasmius cladophyllus produces laccase and lignin peroxidase in glucose minimal liquid medium containing RBBR. Both enzyme activities were increased, with laccase activity recorded 70 times higher reaching up to 390 U L-1 on day 12. Further in vitro RBBR dye decolourisation using the culture medium shows that laccase activity was correlated with the dye decolourisation. Fresh RBBR dye continuously supplemented into the decolourised culture medium was further decolourised much faster in the subsequent round of the RBBR dye decolourisation. In vitro dye decolourisation using the crude laccase not only decolourised 76% of RBBR dye in just 19 hours but also decolourised 54% of Orange G and 33% of Congo red at the same period of time without the use of any exogenous mediator. This rapid dye decolourisation ability of the enzymes produced by M. cladophyllus thus suggested its possible application in the bioremediation of dye containing wastewater